Analysis Modulation Formats in DWDM Transmission System - Li Li; WEI Jian-yi; LI Hong-an; ZHANG Xiu-tai (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
In modulation and demodulation methods of the optical Differential Quadrature Phase Shift Key (DQPSK) and the different modulation formats including nonreturn-to-zero(NRZ), return-to-zero (RZ), carrier-suppressed return-to-zero(CS-RZ) are introduced, studying the different optical signals in the 40Gb/s high speed transmission system. The system is simulated in 200km optical fiber by way of dispersion compensation. It is showed that the ability of anti-dispersion and anti-PMD (Polarization Mode Dispersion) is better in the CS-RZ-DQPSK modulation format, and this format has the smallest eye-opening penalty (EOP) with a wider range of power into the optical fiber. DOI: http://dx.doi.org/10.11591/telkomnika.v11i1.1800